Plates, pyramids and planets: Developments in national healthy and sustainable dietary guidelines: a state of play assessment - Gonzalez Fischer, Carlos Maria (2016)
Our food system and consumption practices have, since prehistoric times, shaped and transformed our world and our societies. There have been enormous advances - in agricultural practice and in systems of storage, distribution and retailing - that have enabled population growth and improved diets for many. But these developments have also carried severe costs. While the tools and actions needed to achieve the necessary changes in diets are many, this publication specifically considers the role of national level dietary guidelines in providing a steer on what dietary patterns that are both healthy and sustainable look like.